Perspectives and experiences of audiologists in India towards counselling - Reshma Stuvert; Dhanshree Rajesh Gunjawate; Rohit Ravi (Elsevier, 2022)
Background: Counselling is very important components of service delivery in clinical work and counselling related skills are crucial. The purpose of the present study was to explore of perspectives and experiences of audiologists in India towards counselling. Methods: Cross sectional online study among audiologists in India. The study was carried out in two phases. The first phase involved developing and validating a questionnaire to explore the perspectives and experiences of audiologists towards counselling. In phase two, 36-item questionnaire was used for data collection. Statistical analysis was carried out using SPSS software version 21 to determine descriptive statistics and the internal consistency of the questionnaire using Cronbach's Alpha. Results: A total of 126 audiologists completed the survey, 61.1% females and 38.9% males. The audiologists were from a wide range of age and experience as well as work settings. The findings suggest that the audiologists considered counselling as an important and inevitable component in the audiologic rehabilitation process. Overall, the audiologists exhibited positive perceptions towards the importance of counselling. Most audiologists expressed the need for a greater emphasis on counselling in curriculum of graduate programs. Conclusion: This study is the first of its kind to explore the experiences and perspectives of audiologists in India towards counselling. Overall, the findings helped in broadening the understanding about the perceptions and experiences of audiologists in India towards counselling.